Genetic Vaccination as a Flexible Tool to Overcome the Immunological Complexity of Invasive Fungal Infections - Luberto, Laura; Neroni, Bruna; Gandini, Orietta; Fiscarelli, Ersilia Vita; Salvatori, Giovanni; Roscilli, Giuseppe; Marra, Emanuele (Frontiers in Microbiology, 2021)
The COVID-19 pandemic has highlighted genetic vaccination as a powerful and cost-effective tool to counteract infectious diseases. Invasive fungal infections (IFI) remain a major challenge among immune compromised patients, particularly those undergoing allogeneic hematopoietic bone marrow transplantation (HSCT) or solid organ transplant (SOT) both presenting high morbidity and mortality rates. Candidiasis and Aspergillosis are the major fungal infections among these patients and the failure of current antifungal therapies call for new therapeutic aids. Vaccination represents a valid alternative, and proof of concept for the efficacy of this approach has been provided at clinical level. This review will analyze current understanding of antifungal immunology, with a particular focus on genetic vaccination as a suitable strategy to counteract these diseases.